Cost Model Estimasi Konseptual Untuk Bangunan Gedung Rumah Sakit - Aptiyasa, Putu A.A.; Effi, Cosmas P.Y Pao; Rada, Stefanus (Teknik Sipil, Politeknik Negeri Ketapangg, 2025)
Implementation of the hospital building project, have a ways of estimation in accordance with the phases of the project. In the early stages of project planning, (owner) requires the estimated cost to construct the project budget. So it is necessary to develop cost estimation model that is easy to use, accurate and reliable. This research planning to develop a model estimation on stage initial project planning, easy with a fairly accurate results. Development method uses the principle of